2020
DOI: 10.35508/jkv.v8i2.3074
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Patologi Anatomi Pada Babi Landrace Suspect African Swine Fever (Asf) Di Kabupaten Kupang

Abstract: African Swine Fever (ASF) is a viral disease that attacks pigs and to date has caused many pig deaths in Kupang Regency. ASF is caused by a double-stranded DNA virus from the Asfivirus genus and the Asfarviridae family. This research aims to determine the anatomical pathology of the swine landrace suspect ASF. Organ samples were collected from two male landrace pigs and two female landrace pigs, aged 7 months, from Oeltuah Village, Taebenu District and Tarus Village, Central Kupang District, Kupang Regency, NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The incidence of bacterial infection was strongly influenced by various factors, including: traditional management systems, multi-species pig farm mixed with other animals, which are potential sources of transmission of Pasteurella sp. [6]. In addition, The highest population density and poor sanitation were very influence the disease incidence [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of bacterial infection was strongly influenced by various factors, including: traditional management systems, multi-species pig farm mixed with other animals, which are potential sources of transmission of Pasteurella sp. [6]. In addition, The highest population density and poor sanitation were very influence the disease incidence [7].…”
Section: Resultsmentioning
confidence: 99%
“…According to [9] stated that the disease caused respiratory problems, stunted growth, and economic losses due to decreased living weight and costs of treatment or prevention. The research was conducted by [6] at the Oeba Slaughterhouse, Kupang, East Nusa Tenggara showed that most infection of the pigs was Pasteurella sp. The generally symptoms showed a mild anorexia, cough and dyspnoea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Logam berat timbal yang bersirkulasi dalam darah dapat menimbulkan reaksi pembentukan reactive oxygen species (ROS) dalam jaringan glomerulus maupun tubulus ginjal. Akibat dari peroksidasi sel-sel glomerulus maupun tubulus, menyebabkan terjadinya nekrosis dan nefritis (Sharma et al, 2014).…”
Section: Pendahuluanunclassified
“…Stres oksidatif terjadi apabila ROS (reactive oxygen species) melebihi jumlah antioksidan untuk melindungi sel terhadap molekul-molekul yang teroksidasi (Lopes et al, 2016). Mekanisme stres oksidatif akibat induksi timbal secara umum adalah dengan merusak membran sel, DNA, dan antioksidan baik pada hewan maupun manusia (Sharma et al, 2014). Timbal dapat menjadi radikal bebas karena timbal memiliki atom bebas yang akan melengkapi lapisan luar timbal menjadi lebih stabil dengan mengikat molekul lain dari tubuh (Dewi et al, 2017).…”
Section: Pembahasanunclassified